# Composition of three functions

## 1 Answer

\[y = 3x - 2=y = 3(3t + 2) - 2=9t+6-2=9t+4\]

\[=9(3k - 2)+4=27k-18+4=27k-14.\]

So

\[y=27k-14=f(k).\]

Erdos

4.4K

Join Matchmaticians Affiliate Marketing
Program to earn up to 50% commission on every question your affiliated users ask or answer.

- 1 Answer
- 139 views
- Pro Bono

### Related Questions

- What can we say about the transformation ?
- Using Substitution to Prove an Big O/upper bound is O(n^3)
- Recursive Set
- Is it true almost all Lebesgue measurable functions are non-integrable?
- Growth of Functions
- Function Invertibility/Inverse & Calculus, One question. Early Uni/College level
- Can someone translate $s_j : \Omega \hspace{3pt} x \hspace{3pt} [0,T_{Final}] \rightarrow S_j \subset R$ into simple English for me?
- Beginner Question on Integral Calculus